The properties of residual water molecules in ionic liquids: a comparison between direct and inverse Kirkwood–Buff approaches - Kobayashi, Takeshi; Reid, Joshua E. S. J.; Shimizu, Seishi; Fyta, Maria; Smiatek, Jens (Physical chemistry chemical physics : PCCP, 2017)
We study the properties of residual water molecules at different mole fractions in dialkylimidazolium based ionic liquids (ILs), namely 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM/BF 4 ) and 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM/BF 4 ) by means of atomistic molecular dynamics (MD) simulations. The corresponding Kirkwood–Buff (KB) integrals for the water–ion and ion–ion correlation behavior are calculated by a direct evaluation of the radial distribution functions. The outcomes are compared to the corresponding KB integrals derived by an inverse approach based on experimental data. Our results reveal a quantitative agreement between both approaches, which paves a way towards a more reliable comparison between simulation and experimental results. The simulation outcomes further highlight that water even at intermediate mole fractions has a negligible influence on the ion distribution in the solution. More detailed analysis on the local/bulk partition coefficients and the partial structure factors reveal that water molecules at low mole fractions mainly remain in the monomeric state. A non-linear increase of higher order water clusters can be found at larger water concentrations. For both ILs, a more pronounced water coordination around the cations when compared to the anions can be observed, which points out that the IL cations are mainly responsible for water pairing mechanisms. Our simulations thus provide detailed insights in the properties of dialkylimidazolium based ILs and their effects on water binding.